Rabanete (Raphanus spp) como fonte de nitrato na produção de linguiça de carne suína defumada - Machado, Adriano Ribeiro (2025)
Recent social and economic changes have significantly influenced consumer behavior, with a growing demand for natural, safe, and additive-free foods, reflecting the increasing interest in functional and “clean label” meat products. In this context, the present study aimed to evaluate the feasibility of using radish powder as a natural alternative to synthetic nitrate/nitrite in the production of smoked pork sausage. Radish powders from Raphanus sativus var. longipinnatus (0.3% and 0.6%) and Raphanus sativus (0.5% and 1%) were applied, and the formulations were subjected to physicochemical, microbiological, color, texture, and sensory analyses at 0, 30, and 60 days of ripening. Microbiological results confirmed the absence of pathogenic and indicator microorganisms in all samples, including positive (C+) and negative (C–) controls, fully meeting the current sanitary standards for fermented meat products. Counts of coagulase-positive Staphylococcus and Escherichia coli remained <1.0 × 10¹ CFU/g, and Salmonella spp. was not detected, ensuring the food safety of the formulations throughout ripening. TBARS results demonstrated that the radish powders maintained lipid oxidation stability during the 60-day period, indicating antioxidant activity of the bioactive compounds present in radish. Color analysis revealed no statistical differences between treatments, showing that the complete replacement of synthetic nitrate/nitrite did not compromise the characteristic coloration of the sausages. Furthermore, sensory analysis indicated that the addition of radish powders did not affect consumer preference, maintaining aroma, flavor, texture, and appearance comparable to the control. In summary, radish powders, particularly RD 0.6%, proved to be a viable technological alternative for the replacement of synthetic nitrate/nitrite in smoked pork sausages, enabling the production of healthier and safer products aligned with current consumer trends. These findings reinforce the industrial potential of radish powder for the development of natural meat products, ensuring sensory quality, microbiological stability, and antioxidant properties without compromising consumer acceptability.